2016
DOI: 10.1126/sciimmunol.aah4576
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus circumvents neutrophils and neutrophil extracellular traps during amniotic cavity invasion and preterm labor

Abstract: Group B streptococci overcome neutrophils in placental membranes, inducing fetal injury and preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 88 publications
0
52
2
2
Order By: Relevance
“…Despite the significant adverse outcomes noted in the GB37-infected group, there was no statistical difference in the peak AF cytokine levels among the three treatment groups of this study (i.e., saline, GB37, and GB37Δ hylB ; Table 1 ). Interestingly, compared to our previously published studies on hyperhemolytic GBSΔ covR -inoculated animals ( 28 ), where we reported peak AF interleukin-6 (IL-6) and IL-8 ranging between 15 and 22 ng/ml (for animals with microbial invasion of the amniotic cavity), the GB37 group had significantly lower peak AF levels of IL-6 ( P = 0.009) and IL-8 ( P = 0.02). Taken together, these results suggest that increased AF cytokines such as IL-6 and IL-8 are not necessarily a predictive signature of preterm labor, particularly during infection with the immunosuppressive hyaluronidase-expressing GBS bacteria.…”
Section: Resultscontrasting
confidence: 62%
See 4 more Smart Citations
“…Despite the significant adverse outcomes noted in the GB37-infected group, there was no statistical difference in the peak AF cytokine levels among the three treatment groups of this study (i.e., saline, GB37, and GB37Δ hylB ; Table 1 ). Interestingly, compared to our previously published studies on hyperhemolytic GBSΔ covR -inoculated animals ( 28 ), where we reported peak AF interleukin-6 (IL-6) and IL-8 ranging between 15 and 22 ng/ml (for animals with microbial invasion of the amniotic cavity), the GB37 group had significantly lower peak AF levels of IL-6 ( P = 0.009) and IL-8 ( P = 0.02). Taken together, these results suggest that increased AF cytokines such as IL-6 and IL-8 are not necessarily a predictive signature of preterm labor, particularly during infection with the immunosuppressive hyaluronidase-expressing GBS bacteria.…”
Section: Resultscontrasting
confidence: 62%
“…To elucidate whether hyaluronidase promotes GBS infection and adverse outcomes during pregnancy, we used a chronically catheterized nonhuman primate ( Macaca nemestrina ) model that closely emulates human pregnancy and defines temporal events during amniotic cavity invasion and preterm labor ( 28 ). Ten animals received choriodecidual inoculations of 1 × 10 8 to 3 × 10 8 CFU of either hyaluronidase-proficient wild-type GBS (strain GB37, n = 5) or an isogenic hyaluronidase-deficient GBS (strain GB37Δ hylB , n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations